EVALUASI TINGKAT KEPUASAN KONSUMEN DALAM PEMBELIAN PRODUK KURMA XYZ DI KOTA SURABAYA - Efendy, Iwan Kurniawan; Widayanti, Sri; Syah, Mirza Andrian (Universitas Nusa Cendana, 2024)
XYZ company encountered business challenges with stagnant sales. Therefore, understanding customer satisfaction is crucial because customer preferences provide essential insights for designing effective marketing strategies to cultivate customer loyalty and compete in the market. This study aimed to identify consumer characteristics, assess consumer satisfaction levels, and evaluate the importance of attributes influencing date palm consumer satisfaction at XYZ outlets in Surabaya City. The research utilized Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) tools, focusing on five variables: Price, Product, Ease of Acquisition, Packaging, and Packaging Design. The CSI calculation revealed a satisfaction score of 60.7%, indicating that consumers were reasonably satisfied with XYZ date products. IPA analysis identified six attributes requiring improvement to better align with customer expectations: affordable product pricing, pricing commensurate with the quality, product taste, product aroma, and branding logos. These findings are instrumental for XYZ in identifying areas that need enhancement to elevate product quality and meet customer expectations effectively. Keywords: Importance Performance Analysis; Customer Satisfaction Index ; Satisfaction; Consumer